Elements to understand the scopes of the principle of typicality in the infringements committed by government officials: notes regarding the judgment of the Constitutional Court in the case of the sanctioning power of the Comptroller General of the Republ - Delgado Contreras, César (2020)
In this article, the author presents to us the basis that were used by the Constitutional Court to declare the unconstitutionality of the legal classification of the offences of the sanctioning power of the Comptroller General of the Republic, for being contrary to the principles of legality and typicality, to later refer to the treatment that the aforementioned principles in the jurisprudence, doctrine and in national legislation have deserved, and finally culminate pointing out the elements that, in their opinion, should have been considered in the resolution of the case to properly address an issue that considers to be central to the legal system, consistent in the standards for the legal classification of the offences in the sanctioning regimes of the personnel that provides services in the State.